2007
DOI: 10.1038/sj.ijo.0803572
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of weight gain in young adults through a seminar-based intervention program

Abstract: Objective: Prevention would be the ideal public health strategy to face the current obesity epidemic. Adoption of healthy lifestyles during the first years of college or university could prevent the onset of weight gain associated with this period of acquired independence and eventually decrease the incidence of obesity. Design: Randomized-controlled trial over a period of 2 years. The subjects received an educational/behavioral intervention (small group seminars) designed to help maintain a healthy lifestyle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
162
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(164 citation statements)
references
References 28 publications
2
162
0
Order By: Relevance
“…In other studies, the activity advice was not clearly reported (12,13,16) . Three studies reported no significant difference in physical activity between groups (13)(14)(15) . One reported no change in fitness but a change in self-reported physical activity (12) .…”
Section: Physical Activitymentioning
confidence: 91%
See 1 more Smart Citation
“…In other studies, the activity advice was not clearly reported (12,13,16) . Three studies reported no significant difference in physical activity between groups (13)(14)(15) . One reported no change in fitness but a change in self-reported physical activity (12) .…”
Section: Physical Activitymentioning
confidence: 91%
“…Usual physical activity was measured using the Canadian Fitness Survey (one study (13) ), the International Physical Activity Questionnaire (IPAQ; one study (18) ) and the Paffenbarger Questionnaire (three studies (15,17,22) ) or an adapted questionnaire (two studies (14,22) ), while four studies used pedometers or motion sensors (17,18,20,22) . Multiple measures of physical activity were used in three studies (13,18,22) . Prescriptive advice on activity was used in three studies which aimed for an energy expenditure of 4200-6300 kJ/ week (1000-1500 kcal/week) or to walk or run four times weekly, and were coupled with ongoing consultation or support to help achieve the activity goals (15,17,22) .…”
Section: Physical Activitymentioning
confidence: 99%
“…The techniques most frequently used were Prompt intention formation, Provide instruction, and Provide information on consequences (see Table 1). Among the remaining 22 techniques, the interventions included an average of six techniques, ranging from none (Hivert, Langlois, Berard, Cuerrier, & Carpentier, 2007) to 13 (Burke, Giangiulio, Gillam, Beilin, & Houghton, 2003).…”
Section: Bctsmentioning
confidence: 99%
“…Behavior change intervention studies targeting the diet and exercise habits of young healthy adults have had mixed results over short follow-up periods (Tully and Cupples 2011;Hivert et al 2007;Calfas et al 2000;Gokee LaRose et al 2010;Jeffery and French 1999;Levine et al 2007;Eiben and Lissner 2005;Lee et al 2011;Poobalan et al 2010). Behavior change interventions personalized to the risk factors, needs, and preferences of individuals have had modest success in preventing weight gain (Gokee LaRose et al 2010;Eiben and Lissner 2005;Lee et al 2011).…”
Section: Discussionmentioning
confidence: 99%